2022
DOI: 10.1590/fst.09922
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the sensory profile of cheese ripeness description by trained and untrained assessors

Abstract: Cheese ripeness is an important step of cheese manufacturing that provides a kind of food with complex sensory characteristics and nuanced differences. The importance of generating rapid/easy consumer perception of a new product is without question. The aim was to evaluate the Santo Giorno cheese sensory profile, at different ripening times and with different starter cultures, evaluated by trained assessors and consumers using CATA questions. The two methods generated similar results. However, the results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(30 reference statements)
0
4
0
Order By: Relevance
“…Finally, the role of sensory methods in the food industry for quality control and product development is important, and the evaluation of the relationships between product formulation, chemical properties, production processes, and sensorial properties can be done by using various statistical techniques (de Lima et al., 2022; Los et al., 2021). In the present study, no sensory evaluation was performed, and it was a limitation in investigating the effects of milk types and ripening periods on the consumer preferences for Antep cheese.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the role of sensory methods in the food industry for quality control and product development is important, and the evaluation of the relationships between product formulation, chemical properties, production processes, and sensorial properties can be done by using various statistical techniques (de Lima et al., 2022; Los et al., 2021). In the present study, no sensory evaluation was performed, and it was a limitation in investigating the effects of milk types and ripening periods on the consumer preferences for Antep cheese.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, they are promising for use in the development of beverages added with probiotic bacteria, but there is a need of performing sensory studies in a further research. Lima et al (2022) highlighted that the importance of generating rapid/easy consumer perception of a new product is an urgent need, and Torres et al (2020) suggested identify consumer needs and expectations, which may assist in developing a new brand, i.e., more competitive products.…”
Section: Viability and In Vitro Resistance Of Lgg To The Git When Car...mentioning
confidence: 99%
“…Consumers are more demanding in relation to meat quality, developing new demands, such as increased shelf life and good sensory quality (Lima et al, 2022). The tenderness of the meat is one of the most important elements in the choice of the product, the modification in the intrinsic structure of the meat, for example, increased proteolysis and fragmentation of the myofibrils contribute to the improvement of tenderness (Alarcon-Rojo et al, 2019;Xiong et al, 2020;Arruda et al, 2021;Araújo et al, 2022).…”
Section: Introductionmentioning
confidence: 99%